"Food made with edible insects": Exploring the social representation of entomophagy where it is unfamiliar. (1st June 2022) - Bisconsin-Júnior, Antônio; Rodrigues, Heber; Behrens, Jorge H.; da Silva, Maria Aparecida Azevedo P.; Mariutti, Lilian Regina B.
Abstract: Insects have attracted much attention as a novel food source because of their environmental and nutritional advantages. In Latin America, some traditional groups consume insects; but the urban areas of Brazil resist adopting insects as food, like most Western countries. Thus, this study investigated the social representation of edible insects to understand the barrier behind this avoidance and to identify their segmentation in the Brazilian population. Seven hundred and eighty individuals were interviewed in all the Brazilian regions. The interview was composed of a word association task, a risk perception evaluation and two open-ended questions about the subject. According to the structural approach of social representation, Disgust was the primary association with edible insects. Three segments of consumers were identified using the risk perception of eating insects. The first segment, composed mainly of young men with higher educational levels, had the lowest risk perception, and the most positive attitude about entomophagy, their associations were also positive, such as Acceptance and Sustainability ; the second had average risk perception and neutral attitude towards edible insects, with neutral and positive associations (e.g., Flavor and Culture ); and the third, formed mostly by older women with lower educational level, presented the highest risk perception and the most negative attitude, and exhibited negative associations ( Disgust, and Fear ). The insect consumption in Brazil would be favored by using species of crickets, grasshoppers, ants, and their fried and roasted styles of preparations. Also, participants would eat insects mainly because of survival and curiosity.